Educational Management In Islamic Framework: Embracing The Prophetic Traditions - Dian, Dian; Oktavia, Raya; Syara Bisyara, Raden (Diroyah : Jurnal Studi Ilmu Hadis, 2023)
This research delves into the conceptualization of educational management within the Islamic framework, specifically through an exploration of the Sunnah or teaching traditions of Prophet Muhammad. The Sunnah of the Prophet inherently encapsulates profound wisdom and pedagogical principles that can aptly serve as a guiding framework for the construction of an efficacious educational system and administration. Fundamental concepts integral to educational management, including meticulous planning, systematic organization, rigorous oversight, visionary leadership, comprehensive evaluation, as well as the underpinning principles of justice and ethics, are discernable within the Sunnah of the Prophet. By means of this inquiry, we endeavor to elucidate the nuanced integration of the Prophet’s educational traditions into the contemporary milieu of Islamic educational management. Methodologically, this study embraces a qualitative paradigm, employing a comprehensive literature review as its primary methodology. Data acquisition is meticulously executed through a systematic documentation process. A compendious corpus of pertinent literature is collected and subsequently subjected to thematic coding, culminating in a comprehensive and holistic data analysis. The findings of this study underscore the imperative necessity of fortifying the foundations of Islamic educational management for the amelioration of educational practices and institutions within the Islamic context. This endeavor necessitates a prior comprehension of the most pertinent and judicious framework for the establishment of Islamic educational management, with a distinct emphasis on its alignment with the prophetic traditions or Sunnah. The principles that the Prophet exemplified inherently embody indispensable tenets that can be posited as paramount preferences in the formulation of a cogent and effective framework for Islamic educational management